ALIH KODE DAN CAMPUR KODE DALAM FILM BATAS KARYA RUDI SOEDJARWO - Maria Astripona; Sisilya Saman Madeten; Amriani Amir (Universitas Tanjungpura, 2020)
Abstract Research on code switching and code mixing in the Batas film by Rudi Soedjarwo is a study in the field of sociolinguistics focused on code switching and code mixing. The formulation of the problem in this research is how the form and the factors causing code switching and code mixing in the Batas film by Rudi Soedjarwo, and the implications of learning in school. This study aims to describe: (1) the form of code switching and code mixing, (2) the factors of code switching and code mixing, (3) the implications of learning in school. The method used in this research is descriptive method and the form of this research is qualitative research. The data source in this study is the Batas film by Rudi Soedjarwo. The data in this study are dialogue quotations that have code switching and code mixing. Data collection techniques in this study are documentary study techniques. The main data collection tool and used is a data card. Based on the results of data analysis, the form of code switching and code mixing contained in the Batas film by Rudi Soedjarwo is internal and external code switching. Meanwhile, the mixed code forms contained in the Batas film by Rudi Soedjarwo are words, phrases and clauses. Keywords: Code Switching, Code Mixing, Form and Factor Code Switching.